Anode active material, its manufacturing method, and device including anode active material

JP7640734B2Active Publication Date: 2025-03-05CONTEMPORARY AMPEREX TECHNOLOGY (HONG KONG) LIMITED
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023558952
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-05-25
Publication Date
2025-03-05
Estimated Expiration
2042-05-25

AI Technical Summary

Benefits of technology

【0006】 これによって、本願の負極活物質を二次電池に用いると、二次電池のサイクル中にケイ素ナノ粒子は体積膨張する可能性があるが、ケイ素ナノ粒子が炭素骨格に付着しているため、炭素骨格はケイ素ナノ粒子の膨張をある程度制限する効果が奏する。特に、炭素-ケイ素複合体の外周領域が0.8≦B1/A1≦2.5を満たす場合、ケイ素ナノ粒子が炭素骨格に均一に付着しており、炭素マトリックス粒子はケイ素ナノ粒子の体積膨張を大幅に制限して、負極活物質の構造安定性を向上させ、二次電池のサイクル特性を向上させることができる。ケイ素ナノ粒子は、比容量が高いため、負極活物質の容量を向上させ、且つ金属イオンの挿入電圧が低く、金属イオンの挿入に有利であり、二次電池のレート特性を向上させることができる。炭素マトリックス粒子は、導電性が良好であるため、負極活物質の導電性を向上させることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007640734000013
    Figure 0007640734000013
  • Figure 0007640734000014
    Figure 0007640734000014
  • Figure 0007640734000015
    Figure 0007640734000015
Patent Text Reader

Abstract

The present application provides a negative electrode active material, a method for producing the same, and a device including the negative electrode active material. The negative electrode active material includes a carbon-silicon composite including carbon matrix particles having a carbon skeleton and silicon nanoparticles attached to the carbon skeleton of the carbon matrix particles, and in the outer peripheral region of the carbon-silicon composite, the mass percentage A1 of carbon element and the mass percentage B1 of silicon nanoparticles satisfy 0.8≦B1 / A1≦2.5. When the negative electrode active material of the present application is used in a secondary battery, the carbon matrix particles significantly suppress the volume expansion of the silicon nanoparticles during the cycle of the secondary battery, thereby improving the structural stability of the negative electrode active material and the cycle characteristics of the secondary battery.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application relates to the field of batteries, and in particular to anode active materials and methods of making same, as well as devices including anode active materials. [Background technology]

[0002] Secondary batteries have characteristics such as high capacity and long life, and are widely used in electronic devices such as mobile phones, laptops, electric bikes, electric cars, electric planes, electric boats, electric car toys, electric boat toys, electric plane toys and electric tools. Since secondary batteries have made great advances, there is a demand for higher secondary battery properties. In order to improve the properties of secondary batteries, it is common to optimize and improve the materials inside the secondary battery, such as the negative electrode active material. The negative electrode active material, as a carrier of metal ions and electrons in the secondary battery, plays a role in storing and releasing energy, and has a non-negligible impact on the properties of the secondary battery.

[0003] However, even if currently improved negative electrode active materials are used in secondary batteries, the cycle characteristics and rate characteristics of the secondary batteries are still poor. Summary of the Invention [Problem to be solved by the invention]

[0004] The present application has been made in view of the above-mentioned problems, and has an object to provide a negative electrode active material, a method for producing the same, and a device including the negative electrode active material. [Means for solving the problem]

[0005] A first aspect of the present application is a carbon matrix particle having a carbon skeleton, and silicon nanoparticles attached to the carbon skeleton of carbon matrix particles. In the outer peripheral region of the carbon-silicon composite, the mass percentage A1 of the carbon element of the carbon-silicon composite relative to the total mass of the carbon-silicon composite and the mass percentage B1 of the silicon element of the carbon-silicon composite relative to the total mass of the carbon-silicon composite satisfy 0.8≦B1 / A1≦2.5, and optionally 1≦B1 / A1≦1.5; Here, the peripheral region of the carbon-silicon composite is a region extending from the outer surface of the carbon-silicon composite toward the inside of the carbon-silicon composite a distance of within r / 2, where r represents the minor axis of the carbon-silicon composite.

[0006] As a result, when the negative electrode active material of the present application is used in a secondary battery, the silicon nanoparticles may expand in volume during the cycle of the secondary battery, but since the silicon nanoparticles are attached to the carbon skeleton, the carbon skeleton has the effect of restricting the expansion of the silicon nanoparticles to a certain extent. In particular, when the outer peripheral region of the carbon-silicon composite satisfies 0.8≦B1 / A1≦2.5, the silicon nanoparticles are uniformly attached to the carbon skeleton, and the carbon matrix particles can significantly restrict the volume expansion of the silicon nanoparticles, improving the structural stability of the negative electrode active material and improving the cycle characteristics of the secondary battery. The silicon nanoparticles have a high specific capacity, which improves the capacity of the negative electrode active material, and the metal ion insertion voltage is low, which is advantageous for the insertion of metal ions, and can improve the rate characteristics of the secondary battery. The carbon matrix particles have good electrical conductivity, which can improve the electrical conductivity of the negative electrode active material.

[0007] In some embodiments, in the central region of the carbon-silicon composite, a mass percentage A2 of the carbon element of the carbon-silicon composite relative to the total mass of the carbon-silicon composite and a mass percentage B2 of the silicon element of the carbon-silicon composite relative to the total mass of the carbon-silicon composite satisfy 1.05≦A2 / B2≦50, optionally 1.05≦A2 / B2≦3, and the central region of the carbon-silicon composite is a region within a distance r / 2 from the geometric center of the carbon-silicon composite.

[0008] As a result, the central region of the silicon-carbon composite of the present invention satisfies 1.05≦A2 / B2≦50, which further improves the uniformity of adhesion of silicon nanoparticles to the carbon skeleton and further improves the structural stability of the negative electrode active material.

[0009] In some embodiments, the mass percentage A of the elemental carbon of the carbon-silicon composite relative to the total mass of the carbon-silicon composite tends to decrease in a direction from the geometric center of the carbon-silicon composite toward the outer surface of the carbon-silicon composite, and the mass percentage B of the elemental silicon of the carbon-silicon composite relative to the total mass of the carbon-silicon composite tends to increase in a direction from the geometric center of the carbon-silicon composite toward the outer surface of the carbon-silicon composite.

[0010] As a result, in the present application, the content of silicon nanoparticles attached to the carbon skeleton gradually increases, leading to a high content of silicon nanoparticles, and thus the capacity of the negative electrode active material can be greatly improved.

[0011] In some embodiments, the mass percentage A of the elemental carbon of the carbon-silicon composite relative to the total mass of the carbon-silicon composite and the mass percentage B of the elemental silicon of the carbon-silicon composite relative to the total mass of the carbon-silicon composite further satisfy 1≦A / B≦3, and more optionally, 1.3≦A / B≦2.

[0012] Therefore, in the present application, when the content of silicon nanoparticles attached to the carbon skeleton satisfies the above range, the content of silicon nanoparticles is high, and the capacity of the negative electrode active material can be greatly improved.The content of carbon matrix particles is moderate, and the conductivity of the negative electrode active material can be improved.

[0013] In some embodiments, the carbon matrix particles include one or more of graphite, soft carbon, and hard carbon, which provide a carbon skeleton structure that serves as a support for attachment of silicon nanoparticles.

[0014] In some embodiments, the carbon skeleton is a porous carbon skeleton and the silicon nanoparticles are within the pores and / or on the surface of the porous carbon skeleton.

[0015] As a result, in the present application, since at least a portion of the silicon nanoparticles are attached within the pores of the porous carbon skeleton, the porous carbon skeleton restricts to a certain extent the volumetric expansion of the silicon nanoparticles within its pores during cycling of the secondary battery, and by restricting the volumetric expansion of the silicon nanoparticles to a certain range, the structural stability of the negative electrode active material can be ensured and the cycle characteristics of the secondary battery can be improved.

[0016] In some embodiments, the porous carbon skeleton comprises pores that extend through the carbon skeleton.

[0017] In some embodiments, the pore size of the pores is 1 nm to 200 nm, and optionally 1 nm to 50 nm. The pores in this pore size range contribute to the attachment of silicon nanoparticles and can effectively limit the volume expansion of the silicon nanoparticles attached in the pores. In addition, the silicon nanoparticles after the volume expansion do not substantially damage the porous carbon skeleton. This ensures the structural stability of the porous carbon skeleton.

[0018] In some embodiments, the porosity of the porous carbon skeleton is 40% to 70%, and optionally 50% to 60%. When the porosity of the porous carbon skeleton satisfies the above range, the volume ratio of the pores in the porous carbon skeleton is high, silicon nanoparticles are attached in the pores, and the silicon nanoparticles and the carbon matrix particles function synergistically to improve the capacity and conductivity of the negative electrode active material.

[0019] In some embodiments, the particle size D of the silicon nanoparticles is D≦10 nm. A small particle size D of the silicon nanoparticles is advantageous for attachment to the surface and / or pores of the carbon skeleton, and the distribution is more uniform, which is advantageous for improving the uniformity of the properties of the entire negative electrode active material.

[0020] In some embodiments, the negative electrode active material further includes a conductive layer covering the carbon-silicon composite. The conductive layer is a continuous layered structure coated on the surface of the carbon-silicon composite, and covers the voids on the surface of the silicon-carbon composite, reducing the specific surface area of ​​the silicon-carbon composite, reducing the risk of side reactions between the silicon-carbon composite and the electrolyte, and improving the structural stability of the silicon-carbon composite. In addition, the above material has excellent electrical conductivity, so that the electrical conductivity of the negative electrode active material can be greatly improved.

[0021] In some embodiments, the thickness of the conductive layer is ≦3.5 μm, and optionally 2.5 μm to 3.3 μm. When the thickness of the conductive layer satisfies the above range, the conductivity of the entire negative electrode active material can be improved, and smooth movement of metal ions in the negative electrode active material can be ensured.

[0022] In some embodiments, the conductive layer includes a carbon layer and / or a conductive polymer layer, and optionally the conductive polymer layer includes one or more of polyaniline, polypyrrole, polyacetylene, polythiophene, polyphenylene sulfide, and polyparaphenylene. The carbon layer is advantageous for uniformly dispersing on the surface of the silicon-carbon composite, and therefore can improve the electrical conductivity of the entire silicon-carbon composite. The conductive polymer layer has a strong bond with the silicon-carbon composite and is not easily peeled off from the silicon-carbon composite, and therefore can improve the structural stability of the negative electrode active material and further improve the electrical conductivity of the negative electrode active material.

[0023] In some embodiments, the average particle diameter Dv50 of the negative electrode active material is 5 μm≦Dv50≦11 μm. When the average particle diameter Dv50 of the negative electrode active material satisfies the above range, the structure of the negative electrode active material becomes stable, and the dynamic properties thereof become good, which is advantageous for improving the initial coulombic efficiency of the negative electrode active material.

[0024] In some embodiments, the average particle diameters Dv90, Dv10, and Dv50 of the negative electrode active material satisfy (Dv90-Dv10) / Dv50≦1.4. When the particle diameter distribution of the negative electrode active material satisfies the above range, the average particle diameter of the entire negative electrode active material is appropriate, the particle diameter distribution is uniform, and it is advantageous for improving the uniformity of the properties of the entire negative electrode active material.

[0025] In some embodiments, the specific surface area BET of the negative electrode active material is BET≦4 m 2 When the specific surface area BET of the negative electrode active material satisfies the above range, the range of the specific surface area is appropriate, the dynamic properties of the negative electrode active material are good, and it is advantageous for the initial coulombic efficiency of the negative electrode active material.

[0026] A second aspect of the present application is a method for producing a negative electrode active material, A step S100 of supplying a gas containing a silicon precursor to carbon matrix particles having a carbon skeleton; and step S200 of producing silicon nanoparticles attached to a carbon skeleton from a silicon precursor by chemical vapor deposition to obtain a carbon-silicon composite. In a central region of the carbon-silicon composite, a mass percentage A2 of the carbon element of the carbon-silicon composite relative to the total mass of the carbon-silicon composite and a mass percentage B2 of the silicon element of the carbon-silicon composite relative to the total mass of the carbon-silicon composite satisfy 1.05≦A2 / B2≦50, and optionally 1.05≦A2 / B2≦3, wherein the central region of the carbon-silicon composite is a region that is within a distance of r / 2 from the geometric center of the carbon-silicon composite, where r represents the minor axis of the carbon-silicon composite; The present invention provides a method for producing a negative electrode active material, wherein in a peripheral region of the carbon-silicon composite, a mass percentage A1 of the carbon element in the carbon-silicon composite relative to the total mass of the carbon-silicon composite and a mass percentage B1 of the silicon element in the carbon-silicon composite relative to the total mass of the carbon-silicon composite satisfy 0.8≦B1 / A1≦2.5, and optionally, 1≦B1 / A1≦1.5, and wherein the peripheral region of the carbon-silicon composite is a region extending from the outer surface of the carbon-silicon composite toward the inside of the carbon-silicon composite a distance of within r / 2.

[0027] As a result, the method according to the embodiment of the present application has a simple manufacturing process and easy adjustment of process conditions. Furthermore, when the negative electrode active material obtained by the method is used in a secondary battery, the secondary battery has good cycle characteristics.

[0028] In some embodiments, the method may further include the step S300 of forming a conductive layer on the silicon-carbon composite. By forming a conductive layer on the surface of the silicon-carbon composite to coat the silicon-carbon composite, the electrical conductivity of the entire negative electrode active material is improved.

[0029] A third aspect of the present application further provides a secondary battery including the anode active material according to any of the embodiments of the first aspect of the present application, or the anode active material produced according to any of the embodiments of the second aspect of the present application.

[0030] A fourth aspect of the present application further provides a battery module including the secondary battery according to the embodiment of the third aspect of the present application.

[0031] A fifth aspect of the present application further provides a battery pack including a battery module according to any of the embodiments of the fourth aspect of the present application.

[0032] A sixth aspect of the present application further provides a power consuming device including a secondary battery according to an embodiment of the third aspect of the present application, a battery module according to an embodiment of the fourth aspect of the present application, or a battery pack according to an embodiment of the fifth aspect of the present application. [Brief description of the drawings]

[0033] In order to better explain the technical solutions of the embodiments of the present application, the drawings used in the embodiments of the present application are briefly described below. Obviously, the drawings described below are only a part of the embodiments of the present application, and those skilled in the art can obtain other drawings based on the drawings without creative efforts. [Figure 1] FIG. 2 is a schematic diagram of a production flow of a negative electrode active material according to an embodiment of the present application. [Diagram 2] FIG. 4 is a schematic diagram of a production flow of a negative electrode active material according to another embodiment of the present application. [Diagram 3] FIG. 2 is a schematic diagram of a manufacturing flow of a negative electrode active material according to a further embodiment of the present application. [Figure 4] FIG. 1 is a schematic diagram of a secondary battery according to an embodiment of the present application. [Diagram 5] FIG. 5 is an exploded view of the secondary battery according to the embodiment of the present application shown in FIG. 4. [Figure 6] FIG. 1 is a schematic diagram of a battery module according to an embodiment of the present application. [Figure 7] FIG. 1 is a schematic diagram of a battery pack according to an embodiment of the present application. [Figure 8] FIG. 8 is an exploded view of the battery pack according to the embodiment of the present application shown in FIG. 7. [Figure 9] 1 is a schematic diagram of a power consuming device according to an embodiment of the present application; [Explanation of symbols]

[0034] The symbols are as follows: 1 Secondary battery 11 Exterior body 111 Top cover assembly 112 cases 12 Electrode Assembly 10 Battery module 20 Battery Pack 21 Upper case 22 Lower housing 30 Power consumption equipment DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0035] Hereinafter, embodiments specifically disclosing the electrolyte, secondary battery, battery, and power consumption device of the present application will be described in detail. However, unnecessary detailed description may be omitted. For example, detailed description of known matters or duplicate description of the same structure may be omitted. This is to avoid the following description from becoming unnecessarily redundant and to facilitate understanding by those skilled in the art. Furthermore, the drawings and the following description are provided to enable those skilled in the art to fully understand the present application, and are not intended to limit the subject matter described in the claims.

[0036] The "ranges" disclosed in this application are defined in the form of lower and upper limits, and a given range is defined by selecting lower and upper limits that define the boundaries of the particular range. The ranges defined in this way may or may not include the end values, and may be arbitrarily combined, i.e., any lower limit value may be combined with any upper limit value to form a range. For example, if the ranges 60-120 and 80-110 are listed for a particular parameter, it can be understood that the ranges 60-110 and 80-120 are also contemplated. Also, if the minimum range values ​​are 1 and 2, and the maximum range values ​​are 3, 4, and 5, the ranges 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5 are all contemplated. In this application, unless otherwise specified, a range of "a to b" represents a shorthand representation of any combination of real numbers between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are recited herein, and "0-5" is an abbreviation for combinations of these numerical values. Also, when a parameter is described as an integer greater than or equal to 2, this corresponds to the disclosure that the parameter is an integer, e.g., 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0037] Unless otherwise specified, all and any embodiments of the present application can be combined with each other to form a new technical solution. Unless otherwise specified, all and any technical features of the present application can be combined with each other to form a new technical solution.

[0038] Unless otherwise stated, all steps in this application may be performed sequentially, randomly, or preferably sequentially. For example, when a method includes steps (a) and (b), it indicates that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, when a method includes a step (c), it indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or may include steps (a), (c), and (b), or may include steps (c), (a), and (b).

[0039] Unless otherwise specified, the terms "comprise", "have", and "comprise" used herein mean open-ended and may also be closed-ended. For example, the terms "comprise", "have", and "comprise" may mean "comprise", "have", or "comprise" other components not listed, or "comprise", "have", or "comprise" only the listed components.

[0040] In this application, the term "or" is inclusive unless otherwise specified. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist). negative electrode active material

[0041] In a first aspect, the present application provides an active anode material, the active anode material comprising a carbon-silicon composite including carbon matrix particles and silicon nanoparticles.

[0042] The carbon matrix particles have a carbon skeleton, which may be a solid structure or a porous skeleton structure having pores.

[0043] In the present application, the pores refer to a recessed structure recessed with respect to the outer surface of the negative electrode active material and recessed into the inside of the negative electrode active material, or through-holes penetrating the negative electrode active material. The porous skeleton structure refers to a plurality of pores in the negative electrode active material, and the plurality of pores may be arranged parallel and / or cross each other. The porous structure includes parameters such as pore size, pore length, and pore size distribution. The pore sizes of the porous carbon skeleton of the carbon matrix particles include micropores, mesopores, and macropores. The micropores are pores with a diameter of less than about 2 nm. The mesopores are pores with a diameter of about 2 nm to about 5 nm. The macropores are pores with a diameter of more than 50 nm.

[0044] The particle size of the silicon nanoparticles is on the nanoscale, which makes it easier for the silicon nanoparticles to be uniformly attached to the carbon skeleton when the silicon nanoparticles are formed on the carbon skeleton.

[0045] When the carbon skeleton is a solid structure, the silicon nanoparticles may be attached to at least a portion of the surface of the carbon skeleton. When the carbon skeleton is a porous skeleton structure, the silicon nanoparticles may be attached to at least a portion of the surface of the carbon skeleton and within the pores of the carbon skeleton, or the silicon nanoparticles may substantially fill all of the pores of the carbon skeleton.

[0046] A carbon-silicon composite is formed by combining carbon matrix particles and silicon nanoparticles, and the carbon-silicon composite may be a particle with an irregular geometric shape. In this case, the particle size can be characterized using a three-axis diameter characterization method. As a specific characterization method, the long axis l and short axis r are measured on a plane projection of the carbon-silicon composite, and the thickness h of the carbon-silicon composite is measured in the perpendicular direction to the projection plane. It can also be understood that the silicon-carbon composite is placed in a rectangular parallelepiped that is in contact with it, and the long side of the rectangular parallelepiped is l, the short side is r, and the thickness is h, which reflects the actual dimensions of the silicon-carbon composite.

[0047] The silicon-carbon composite includes a central region, a peripheral region, and a transition region between the central and peripheral regions. The central region is considered to be the region within a distance of r / 2 from the geometric center of the silicon-carbon composite. The peripheral region is considered to be the region extending from the outer surface of the silicon-carbon composite toward the interior of the silicon-carbon composite within a distance of r / 2.

[0048] When a silicon-carbon composite includes a recessed structure that is recessed relative to the surface of the silicon-carbon composite, for purposes of this application, the surface of the recessed structure is considered to be an internal structure of the silicon-carbon composite, rather than an external surface of the silicon-carbon composite.

[0049] The outer peripheral region of the silicon-carbon composite has a large amount of silicon nanoparticles attached, and the mass percentage A1 of the carbon element in the carbon-silicon composite relative to the total mass of the carbon-silicon composite and the mass percentage B1 of the silicon element in the carbon-silicon composite relative to the total mass of the carbon-silicon composite satisfy 0.8≦B1 / A1≦2.5.

[0050] When A1 and B1 satisfy the above range, the mass of silicon nanoparticles attached to the inside of the carbon matrix particles is high, the capacity of the negative electrode active material is greatly improved, and the metal ion insertion voltage is low, which is favorable for the insertion of metal ions, and the rate characteristics of the secondary battery can be improved. In addition, the carbon matrix particles can greatly limit the volume expansion of the silicon nanoparticles, improve the structural stability of the negative electrode active material, and improve the cycle characteristics of the secondary battery. Alternatively, 1≦B1 / A1≦1.5. As an example, B1 / A1 may be 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, or 2.5, or may be a range consisting of any two of the above values.

[0051] When the above-mentioned negative electrode active material is used in a secondary battery, the silicon nanoparticles may expand in volume during the cycle of the secondary battery, but since the silicon nanoparticles are attached to the carbon skeleton, the carbon skeleton has the effect of suppressing the expansion of the silicon nanoparticles to a certain extent. In particular, when the outer peripheral region of the carbon-silicon composite satisfies 0.8≦B1 / A1≦2.5, the carbon matrix particles can significantly suppress the volume expansion of the silicon nanoparticles, improve the structural stability of the negative electrode active material, and improve the cycle characteristics of the secondary battery. The silicon nanoparticles have a high specific capacity, which improves the capacity of the negative electrode active material, and a low metal ion insertion voltage, which is advantageous for the insertion of metal ions, and can improve the rate characteristics of the secondary battery. The carbon matrix particles have good conductivity, which can improve the conductivity of the negative electrode active material.

[0052] In some embodiments, the adhesion of silicon nanoparticles to carbon matrix particles has a certain distribution tendency. In the central region of the silicon-carbon composite, the adhesion amount of silicon nanoparticles is small, and the mass percentage A2 of the carbon element of the carbon-silicon composite relative to the total mass of the carbon-silicon composite and the mass percentage B2 of the silicon element of the carbon-silicon composite relative to the total mass of the carbon-silicon composite satisfy 1.05≦A2 / B2≦50.

[0053] When A2 and B2 satisfy the above range, the mass of silicon nanoparticles attached to the inside of the carbon matrix particles is low, and the carbon matrix particles have a good expansion reducing effect on the silicon nanoparticles during the cycle of the secondary battery, which can improve the structural stability of the negative electrode active material and improve the cycle characteristics of the secondary battery. With the decrease of A2 / B2, the content of silicon nanoparticles attached to the carbon matrix particles increases, which improves the capacity of the negative electrode active material, and the metal ion insertion voltage is low, which is favorable for the insertion of metal ions, and the rate characteristics of the secondary battery can be improved. Optionally, 1.05≦A2 / B2≦3. As an example, A2 / B2 may be 1.05, 1.1, 1.15, 1.20, 1.25, 1.30, 1.40, 1.50, 1.60, 1.70, 1.80, 1.90, 2.0, 2.2, 2.5, 2.8, 3.0, 5, 10, 15, 20, 25, 30, 35, 40, 45 or 50, or may be a range consisting of any two of the above values.

[0054] When the central region of the silicon-carbon composite of the present invention satisfies 1.05≦A2 / B2≦50, the degree of uniform attachment of silicon nanoparticles to the carbon skeleton can be further improved, and the structural stability of the negative electrode active material can be further improved.

[0055] In some examples, the mass percentage A of the elemental carbon of the carbon-silicon composite relative to the total mass of the carbon-silicon composite tends to decrease in a direction from the geometric center of the carbon-silicon composite toward the outer surface of the carbon-silicon composite, and the mass percentage B of the elemental silicon of the carbon-silicon composite relative to the total mass of the carbon-silicon composite tends to increase in a direction from the geometric center of the carbon-silicon composite toward the outer surface of the carbon-silicon composite.

[0056] Although the silicon-carbon composite may have an irregular shape, the geometric center of the silicon-carbon composite may be equivalent to the geometric center of a rectangular parallelepiped that is tangent to it. In the direction from the geometric center of the silicon-carbon composite to the outer surface of the silicon-carbon composite, the mass percentage A of the carbon element gradually decreases, and the mass percentage B of the silicon element gradually increases, that is, the content of the silicon nanoparticles attached to the carbon skeleton gradually increases, and the content of the silicon nanoparticles increases, so that the capacity of the negative electrode active material can be greatly improved.

[0057] Alternatively, the mass percentage A of the carbon element of the carbon-silicon composite relative to the total mass of the carbon-silicon composite and the mass percentage B of the silicon element of the carbon-silicon composite relative to the total mass of the carbon-silicon composite further satisfy 1≦A / B≦3, and more preferably 1.3≦A / B≦2. As an example, A / B may be 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.8, 2.0, 2.1, 2.2, 2.3, 2.5, 2.8, or 3, or may be a range consisting of any two of the above numerical values.

[0058] In some embodiments, the carbon matrix particles include one or more of graphite, soft carbon, and hard carbon. In one example, the carbon matrix particles can include hard carbon. Such carbon matrix particles provide a carbon skeleton structure that serves as a support for attachment of silicon nanoparticles.

[0059] In some embodiments, the carbon skeleton may be a porous carbon skeleton. The porous carbon skeleton includes pores, and the silicon nanoparticles may be attached to the surface of the carbon skeleton, or may be filled within the pores. In other words, the silicon nanoparticles are in the pores and / or on the surface of the porous carbon skeleton.

[0060] When the negative electrode active material is used in a secondary battery, at least a portion of the silicon nanoparticles are attached within the pores of the porous carbon skeleton, and therefore, during the cycle of the secondary battery, the porous carbon skeleton restricts to a certain extent the volumetric expansion of the silicon nanoparticles within its pores, thereby restricting the volumetric expansion of the silicon nanoparticles to a certain range, thereby ensuring the structural stability of the negative electrode active material and improving the cycle characteristics of the secondary battery.

[0061] In some embodiments, the porous carbon skeleton has pores penetrating the skeleton, and the silicon nanoparticles attached to the pores are advantageous in that the silicon nanoparticles are uniformly attached to each region of the porous carbon skeleton, and the volumetric expansion of silicon in each region of the silicon-carbon composite is substantially consistent, thereby improving the uniformity of the properties of each region of the porous carbon skeleton and improving the uniformity of the properties of the overall anode active material.

[0062] In some embodiments, the pores of the porous carbon skeleton have a nanopore size, and the pores in this size range are conducive to the attachment of silicon nanoparticles and can effectively limit the volume expansion of the silicon nanoparticles attached in the pores, and the silicon nanoparticles after the volume expansion do not substantially damage the porous carbon skeleton, thereby ensuring the structural stability of the porous carbon skeleton.

[0063] Alternatively, the pores of the porous carbon skeleton may have a pore size of 1 nm to 200 nm, and more preferably, 1 nm to 50 nm. As an example, the pores of the porous carbon skeleton may have a pore size of 1 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 120 nm, 150 nm, 180 nm, or 200 nm, or may be in a range consisting of any two of the above values.

[0064] In some embodiments, the porosity of the porous carbon skeleton is between 40% and 70%.

[0065] The porosity of a porous carbon skeleton is the ratio of the volume of the pores in the porous carbon skeleton to the total volume of the porous carbon skeleton.

[0066] When the porosity of the porous carbon skeleton satisfies the above range, the volume of the pores in the porous carbon skeleton is large, silicon nanoparticles are attached to the inside of the pores, and the silicon nanoparticles and the carbon matrix particles function synergistically, thereby improving the capacity and conductivity of the negative electrode active material. Alternatively, the porosity of the porous carbon skeleton may be 50% to 60%. As an example, the porosity of the porous carbon skeleton may be 40%, 42%, 45%, 48%, 50%, 52%, 55%, 58%, 60%, 62%, 65%, 68%, 70%, or may be in a range consisting of any two of the above values.

[0067] In this application, the introduction of porosity into the carbon matrix particles can be achieved in various ways, for example, by adjusting the processing conditions, the porosity of the carbon matrix particles can be achieved to produce a porous carbon skeleton.

[0068] In some embodiments, the particle size D of the silicon nanoparticles satisfies D≦10 nm.

[0069] Silicon nanoparticles have a small particle size D, which makes it easier to attach to the surface and / or pores of the carbon skeleton. In addition, their distribution is more uniform, which is advantageous for improving the uniformity of the properties of the entire negative electrode active material. As an example, D may be 10 nm, 8 nm, 6 nm, 5 nm, 4 nm, 3 nm, 2 nm, or 1 nm.

[0070] In some embodiments, the negative electrode active material may further include a conductive layer coating the carbon-silicon composite. The conductive layer is a continuous structure coated on the surface of the carbon-silicon composite, and can connect discontinuous regions of the composite to improve the electrical conductivity of the entire negative electrode active material.

[0071] When the silicon-carbon composite has a solid structure, the conductive layer is coated on the surface of the silicon-carbon composite, thereby improving the conductivity of the entire negative electrode active material. When the silicon-carbon composite includes a porous carbon skeleton, silicon nanoparticles are filled in the pores of the porous carbon skeleton, so that the entire silicon-carbon composite has a solid structure, and the conductive layer is coated on the surface of the silicon-carbon composite, so that the surface of the negative electrode active material becomes a continuous conductive surface, thereby improving the conductivity of the negative electrode active material.

[0072] In some embodiments, the conductive layer may include a carbon layer and / or a conductive polymer layer. The conductive layer is a continuous layered structure coated on the surface of the carbon-silicon composite, and can cover the voids on the surface of the silicon-carbon composite, reduce the specific surface area of ​​the silicon-carbon composite, reduce the risk of side reactions between the silicon-carbon composite and the electrolyte, and improve the structural stability of the silicon-carbon composite. In addition, the above material has excellent electrical conductivity, so that the electrical conductivity of the negative electrode active material can be greatly improved.

[0073] As some examples, the carbon layer may include carbon particles, which are advantageous in that the carbon particles have a small particle size and are uniformly dispersed on the surface of the silicon-carbon composite, thereby improving the electrical conductivity of the entire silicon-carbon composite.

[0074] As some other examples, the conductive polymer layer may include one or more of polyaniline, polypyrrole, polyacetylene, polythiophene, polyphenylene sulfide, and polyparaphenylene. Such a conductive polymer layer has a strong bond with the silicon-carbon composite and is not easily peeled off from the silicon-carbon composite, so that the structural stability of the negative electrode active material can be improved and the conductivity of the negative electrode active material can be further improved.

[0075] In some embodiments, the conductive layer may have a thickness of ≦3.5 μm, optionally between 2.5 μm and 3.3 μm.

[0076] When the thickness of the conductive layer satisfies the above range, the conductivity of the entire negative electrode active material can be improved and smooth movement of metal ions in the negative electrode active material can be ensured. Alternatively, the thickness of the conductive layer may be 2.5 μm to 3.3 μm, and as an example, the thickness of the conductive layer may be 1 μm, 1.5 μm, 2.0 μm, 2.5 μm, 3 μm, 3.3 μm, or 3.5 μm, or may be within a range consisting of any two of the above values.

[0077] In some embodiments, the negative electrode active material has an average particle size Dv50 of 5 μm≦Dv50≦11 μm.

[0078] The Dv50 value of the negative electrode active material means the median particle size of the negative electrode active material. Specifically, a certain Dv50 value means that the particle size of the particles that occupy 50% of the total volume is larger than this value, or the particle size of the particles that occupy 50% of the total volume is smaller than this value. The Dv50 value of the negative electrode active material can be measured with reference to the method specified in GB / T19077-2016.

[0079] When the average particle diameter Dv50 of the negative electrode active material satisfies the above range, the structure of the negative electrode active material is stable, the dynamic characteristics are good, and it is advantageous to improve the initial coulombic efficiency of the negative electrode active material. As an example, the average particle diameter Dv50 of the negative electrode active material may be 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, or 11 μm, or may be within a range consisting of any two of the above values.

[0080] Alternatively, the average particle diameters Dv90, Dv10 and Dv50 of the negative electrode active material satisfy (Dv90-Dv10) / Dv50≦1.4.

[0081] (Dv90-Dv10) / Dv50 represents the particle size distribution spin of the negative electrode active material.

[0082] The Dv10 value of the negative electrode active material represents the particle size corresponding to 10% of the volume distribution in the particles, specifically, the particle size of the particles that occupy 10% of the total volume of the particles is larger than this value, or the particle size of the particles that occupy 90% of the total volume is smaller than this value. The Dv10 value of the negative electrode active material can be measured with reference to the method specified in GB / T19077-2016.

[0083] The Dv90 value of the negative electrode active material represents the particle size corresponding to 90% of the volume distribution in the particles, and the Dv90 value means that the particle size of the particles that occupy 90% of the total volume is larger than this value, or the particle size of the particles that occupy 10% of the total volume is smaller than this value. The Dv90 value of the negative electrode active material can be measured with reference to the method specified in GB / T19077-2016.

[0084] When the particle size distribution of the negative electrode active material satisfies the above range, the average particle size of the entire negative electrode active material is appropriate. In addition, the particle size distribution is uniform, which is advantageous for improving the uniformity of the properties of the entire negative electrode active material. As an example, (Dv90-Dv10) / Dv50 may be 1.4, 1.3, 1.2, 1.1, 1, or 0.75, and of course, may be a range consisting of any two of the above values. In the process of producing the negative electrode active material, the particle size distribution of the negative electrode active material can be controlled by pulverizing the negative electrode active material collectively using ball mill beads of multiple diameters.

[0085] In some embodiments, the specific surface area BET of the negative electrode active material is BET≦4 m 2 / g.

[0086] Specific surface area means the total specific surface area of ​​a material that can be measured by the BET technique. Surface area is usually measured in m 2 It is expressed in units of / g. The BET (Brunauer / Emmett / Teller) technique uses an inert gas (e.g., nitrogen gas) to measure the amount of gas adsorbed on the negative electrode active material and is commonly used in the art to determine the accessible surface area of ​​the material.

[0087] When the specific surface area BET of the negative electrode active material satisfies the above range, the specific surface area range is appropriate, the dynamic properties of the negative electrode active material are good, and the initial coulombic efficiency of the negative electrode active material is favorable. For example, the BET is 4m 2 / g, 3.5m 2 / g, 3m 2 / g, 2.5m 2 / g, 2m 2 / g, 1.5m 2 / g, 1m 2 / g or 0.75m 2 / g, but of course it may be a range consisting of any two of the above values. Method for producing negative electrode active material

[0088] In a second aspect, the present application further provides a method for producing a negative electrode active material according to any of the embodiments of the first aspect of the present application.

[0089] As shown in Figure 1, this method specifically includes: A step S100 of supplying a gas containing a silicon precursor to carbon matrix particles having a carbon skeleton; and step S200 of producing silicon nanoparticles attached to a carbon skeleton from a silicon precursor by chemical vapor deposition to obtain a silicon-carbon composite.

[0090] The silicon precursor is deposited on the carbon skeleton by chemical vapor deposition to form silicon nanoparticles, and the carbon matrix particles and the silicon nanoparticles are combined to form a silicon-carbon composite. The carbon and silicon elements work synergistically to improve the conductivity and capacity of the negative electrode active material, and the carbon matrix particles can limit the volume expansion of the silicon nanoparticles to a certain extent to ensure the structural stability of the negative electrode active material.

[0091] In particular, when the negative electrode active material satisfies the requirement that, in the outer peripheral region of the carbon-silicon composite, the mass percentage A1 of the carbon element in the carbon-silicon composite relative to the total mass of the carbon-silicon composite and the mass percentage B1 of the silicon element in the carbon-silicon composite relative to the total mass of the carbon-silicon composite satisfy 0.8≦B1 / A1≦2.5, and optionally 1≦B1 / A1≦1.5, the carbon element and the silicon element can function more synergistically, thereby improving the structural stability and capacity of the negative electrode active material.

[0092] In step S100, carbon matrix particles may be placed in the heating chamber of the vapor deposition furnace in advance, and the heating chamber may be evacuated using a vacuum pump. A protective gas is introduced into the heating chamber, and after the heating chamber is filled with the protective gas, a gas containing a silicon precursor is introduced into the heating chamber and the heating chamber is maintained at a constant pressure.

[0093] In the present application, inert gas and / or hydrogen gas are adopted as protective gas, and protective gas and gas containing silicon precursor can be introduced into carbon matrix particles together.As an example, the inert gas can include one or more of nitrogen gas, argon gas and helium gas.As an example, the gas containing silicon precursor includes one or more of silane, dichlorosilane, trichlorosilane and tetrachlorosilane.

[0094] In the present application, the deposition effect can be improved by controlling the deposition conditions. In particular, when the carbon matrix particles include a porous carbon skeleton, the uniformity of the deposition of silicon nanoparticles in the pores of the porous carbon skeleton can be adjusted, so that the porous carbon skeleton can further reduce the expansion volume of the silicon nanoparticles, thereby improving the cycle characteristics of the secondary battery. In addition, the silicon nanoparticles deposited on the porous carbon skeleton do not substantially aggregate, so that the cycle characteristics of the secondary battery can be ensured.

[0095] In some embodiments, the gas flow ratio of the silicon precursor containing gas to the protective gas may be (1-10):1.

[0096] In some embodiments, the temperature of the heating chamber is raised to 450° C. to 1000° C. and kept at that temperature for 2 h to 10 h, and the pressure inside the furnace is set to a positive pressure.

[0097] In some embodiments, the heating chamber is evacuated to a relative vacuum of 100 Pa to 800 Pa, and is provided with a rotation function, with the rotation speed controlled to 0.5 r / min to 3 r / min.

[0098] In S200, during the chemical vapor deposition, the silicon precursor can be decomposed into silicon nanoparticles by heating and deposited on the carbon matrix particles. When the carbon matrix particles include a porous carbon skeleton, the silicon nanoparticles can be deposited in the pores and / or on the surface of the porous carbon skeleton.

[0099] After the heating chamber is kept warm, the introduction of the gas containing the silicon precursor is stopped, and after the formed silicon nanoparticles are naturally cooled, the introduction of the protective gas is stopped. The carbon-silicon composite formed in step S200 can be the final product of the negative electrode active material. Of course, after the step S200 is completed, other steps such as step S510 and / or S300 may be performed to further improve the properties of the negative electrode active material.

[0100] As shown in FIG. 2 , in some embodiments, a method for producing a negative electrode active material includes: The method may further include a step S300 of forming a conductive layer on the silicon-carbon composite.

[0101] The conductive layer may include a carbon layer and / or a conductive polymer layer. By forming a conductive layer on the surface of the silicon-carbon composite to cover the silicon-carbon composite, the conductivity of the entire negative electrode active material is improved.

[0102] The silicon-carbon composite formed in step S300 can be the final product of the negative electrode active material. Of course, after step S300 is completed, other steps such as step S520 may be performed to further improve the properties of the negative electrode active material.

[0103] In some examples, when forming the carbon layer, a carbon layer may be produced by chemical vapor deposition using a hydrocarbon-based gas as a carbon source, and coated on the surface of the silicon-carbon composite. In some examples, the hydrocarbon-based gas may include C1-C3 linear alkanes, cyclopropane, C2-C3 alkenes, and C2-C3 alkynes. As an example, the C1-C3 linear alkanes may include one or more of methane, ethane, and propane. The C2-C3 olefins may include ethylene and / or propylene. The C2-C3 alkynes may include acetylene and / or propylene.

[0104] In the present invention, the carbon layer can be formed under a protective atmosphere, and the protective gas can be nitrogen gas or argon gas.

[0105] The present application improves the deposition effect by controlling the deposition conditions, covers the voids on the surface of the silicon-carbon composite, reduces the specific surface area of ​​the negative electrode active material, and improves the electrical conductivity of the negative electrode active material.

[0106] In some embodiments, the gas flow ratio of the hydrocarbon gas to the protective gas is 1:(1.5-10).

[0107] In some embodiments, the temperature is controlled to 750° C.-950° C. during the process of forming the carbon layer, and the coating time is controlled to 2 h-8 h.

[0108] As some other examples, when forming a conductive polymer layer, the organic polymer may be dissolved in a solvent by a solvent method, then uniformly mixed with the carbon-silicon composite, and the solvent may be removed to form the organic polymer into a conductive polymer layer coated on the surface of the silicon-carbon composite. As an example, the organic polymer may include one or more of polyaniline, polypyrrole, polyacetylene, polythiophene, polyphenylene sulfide, and polyparaphenylene. The solvent may include acetone, methanol, or the like. The present application improves the coating effect by controlling the coating conditions, covers the voids on the surface of the silicon-carbon composite, reduces the specific surface area of ​​the negative electrode active material, and improves the conductivity of the negative electrode active material.

[0109] In some embodiments, the method for producing an anode active material may further include a step S500 of screening the silicon-carbon composite to isolate the anode active material that fits within a preset particle size range.

[0110] The screening step of step S500 may include step S510, which is performed after step S200.

[0111] S510: A first screening is performed on the silicon-carbon composite to separate silicon-carbon composites that meet a first preset particle size range. This step can remove those on which silicon nanoparticles are not deposited. As an example, the first preset particle size range may be Dv10≧1.5 μm. In the first screening process, silicon-carbon composites with small particle sizes can be removed, so that the particle size distribution of the silicon-carbon composites can be made uniform. The silicon-carbon composite obtained after the first screening process can be used as a finished product of the negative electrode active material. Of course, after the first screening process is completed, the process may be continued by other steps such as step S300 in order to further improve the properties of the negative electrode active material.

[0112] The screening step of step S500 may further include step S520, which is performed after step S300.

[0113] S520: A second screening is performed on the silicon-carbon composite to separate silicon-carbon composites that meet a second preset particle size range. As an example, the second preset particle size range may be 5 μm≦Dv50≦11 μm.

[0114] As shown in FIG. 3, in some embodiments, the method for producing a negative electrode active material further includes a step S400 of producing carbon matrix particles including a porous carbon skeleton, specifically, the production process includes steps S410 to S440.

[0115] S410: Crushing biomass as a carbon source. One or more of coconut shells, bark, and fruit kernels can be used as the biomass.

[0116] S420: The pulverized biomass is washed with an inorganic acid, which may be one or more of sulfuric acid, hydrochloric acid, and hydrofluoric acid. The concentration of the inorganic acid is 1 mol / L to 5 mol / L, and the pickling time is 0.5 h to 2 h.

[0117] S430: After the acid washing, the biomass is washed with deionized water to remove residual acid, and then the biomass is pre-carbonized in an inert atmosphere. The inert gas may be one or more selected from nitrogen gas, argon gas, and helium gas. The pre-carbonization temperature is 400 to 500°C, and the pre-carbonization time is 2 to 5 hours.

[0118] S440: The pre-carbonized biomass is carbonized at high temperature to obtain a porous carbon material. The carbonization temperature is 800°C to 1600°C, and the carbonization time is 2h to 4h.

[0119] Depositing silicon nanoparticles in the porous carbon skeleton is more advantageous for restricting the volume expansion of silicon nanoparticles by the porous carbon skeleton, ensuring the structural stability of the negative electrode active material.

[0120] In the present application, the pore size, porosity, etc. of the porous carbon skeleton can be adjusted by controlling the change in at least one of the pickling concentration, pickling time, pre-carbonization temperature, pre-carbonization time, carbonization temperature, and carbonization time. secondary battery

[0121] In a third aspect, the present application provides a secondary battery. The secondary battery of the present application may further include a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte. The separator is disposed between the positive electrode sheet and the negative electrode sheet to separate the positive electrode sheet and the negative electrode sheet. [Negative electrode sheet]

[0122] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer provided on at least one surface of the negative electrode current collector. The negative electrode active material layer includes a negative electrode active material.

[0123] As an example, the negative electrode current collector has two surfaces opposing each other in the thickness direction thereof, and the negative electrode active material layer is provided on one or both of the two opposing surfaces of the negative electrode current collector.

[0124] In some embodiments, the negative electrode current collector can be a metal foil or a composite current collector. The metal foil can be, for example, a copper foil. The composite current collector can include a polymeric substrate layer and a metal layer formed on at least one surface of the polymeric substrate layer. The composite current collector can be formed by forming a metal material (such as copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys) on a polymeric substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0125] In some embodiments, the anode active material may include an anode active material according to any embodiment of the first aspect of the present application, or may be an anode active material produced by a method according to any embodiment of the second aspect of the present application.

[0126] In the secondary battery of the present application, the carbon skeleton has the effect of suppressing the expansion of the silicon nanoparticles to a certain extent during cycling. In particular, when the peripheral region of the carbon-silicon composite satisfies 0.8≦B1 / A1≦2.5, the carbon matrix particles can greatly restrict the volume expansion of the silicon nanoparticles, improve the structural stability of the negative electrode active material, and further improve the cycle characteristics of the secondary battery. The silicon nanoparticles have a high specific capacity, which improves the capacity of the negative electrode active material, and have a low metal ion insertion voltage, which is advantageous for the insertion of metal ions, and can improve the rate characteristics of the secondary battery. The carbon matrix particles have good electrical conductivity, which can improve the electrical conductivity of the negative electrode active material.

[0127] In some embodiments, the negative electrode active material layer may optionally include a binder, which may be at least one selected from styrene butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0128] In some embodiments, the negative electrode active material layer may optionally further include a conductive agent, which may be at least one selected from superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0129] In some embodiments, the negative electrode active material layer may optionally further include other auxiliary agents, such as a thickening agent (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0130] In some examples, the negative electrode sheet can be manufactured by dispersing the above-mentioned components for manufacturing a negative electrode sheet, such as a negative electrode active material, a conductive agent, a binder, and any other components, in a solvent (e.g., deionized water) to form a negative electrode slurry, applying the negative electrode slurry onto a negative electrode current collector, and obtaining a negative electrode sheet through processes such as drying and cold pressing. [Positive electrode sheet]

[0131] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer provided on at least one surface of the positive electrode current collector. The positive electrode active material layer includes a positive electrode active material.

[0132] As an example, the positive electrode current collector has two surfaces opposing each other in the thickness direction thereof, and the positive electrode active material layer is provided on one or both of the two opposing surfaces of the positive electrode current collector.

[0133] In some embodiments, the positive electrode current collector can be a metal foil or a composite current collector. The metal foil can be, for example, an aluminum foil. The composite current collector can include a polymeric substrate layer and a metal layer formed on at least one surface of the polymeric substrate layer. The composite current collector can be formed by forming a metal material (such as aluminum, aluminum alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys) on a polymeric substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0134] In some embodiments, the positive electrode active material may be a positive electrode active material for batteries known in the art. As an example, the positive electrode active material may include at least one of lithium-containing phosphates having an olivine structure, lithium transition metal oxides, and modified compounds thereof. However, the present application is not limited to these materials, and other conventional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Here, examples of lithium transition metal oxides include lithium cobalt oxide (e.g., LiCoO2), lithium nickel oxide (e.g., LiNiO2), lithium manganese oxide (e.g., LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (e.g., LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (abbreviated as NCM 333 ), LiNi 0.5 Co 0.2 Mn 0.3 O2 (abbreviated as NCM 523 ), LiNi 0.5 Co 0.25 Mn 0.25 O2 (abbreviated as NCM 211 ), LiNi 0.6 Co 0.2 Mn 0.2 O2 (abbreviated as NCM 622 ), LiNi 0.8 Co 0.1 Mn 0.1 O2 (abbreviated as NCM 811 ), lithium nickel cobalt aluminum oxide (e.g. LiNi 0.85 Co 0.15 Al 0.05Examples of lithium-containing phosphates having an olivine structure include, but are not limited to, at least one of lithium iron phosphate (e.g., LiFePO4 (abbreviated as LFP)), lithium iron phosphate and carbon composite, lithium manganese phosphate (e.g., LiMnPO4), lithium manganese phosphate and carbon composite, lithium manganese iron phosphate, and lithium manganese iron phosphate and carbon composite.

[0135] In some embodiments, the positive electrode active material layer may further include a binder. For example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), a terpolymer of vinylidene fluoride-tetrafluoroethylene-propylene, a terpolymer of vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene, a copolymer of tetrafluoroethylene-hexafluoropropylene, and a fluorine-containing acrylate resin.

[0136] In some embodiments, the positive electrode active material layer may optionally further include a conductive agent. For example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Cochen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0137] In some examples, the positive electrode sheet can be manufactured by dispersing the above-mentioned components for manufacturing a positive electrode sheet, such as a positive electrode active material, a conductive agent, a binder, and any other components, in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry, applying the positive electrode slurry to a positive electrode current collector, and obtaining a positive electrode sheet through processes such as drying and cold pressing. [Separator]

[0138] In some embodiments, the secondary battery further includes a separator. In the present application, the type of the separator is not particularly limited, and any known porous structure separator having good chemical stability and mechanical stability can be selected.

[0139] In some embodiments, the separator may be made of at least one material selected from glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator may be a single-layer thin film or a multi-layer composite thin film, and is not particularly limited. When the separator is a multi-layer composite thin film, the materials of each layer may be the same or different, and is not particularly limited.

[0140] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be formed into an electrode assembly by a winding process or a lamination process. [Electrolyte]

[0141] The electrolyte serves to conduct ions between the positive electrode sheet and the negative electrode sheet. In the present application, the type of the electrolyte is not particularly limited and can be selected according to requirements. For example, the electrolyte may be liquid, gel, or all solid.

[0142] In some embodiments, the electrolyte is an electrolytic solution, which includes an electrolyte salt and a solvent.

[0143] In some embodiments, the electrolyte salt can be at least one selected from lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bisfluorosulfonylimide, lithium bistrifluoromethanesulfonylimide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluoro(oxalato)borate, lithium bis(oxalato)borate, lithium difluorobis(oxalato)phosphate, and lithium tetrafluoro(oxalato)phosphate.

[0144] In some embodiments, the solvent may be at least one selected from ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.

[0145] In some embodiments, the electrolyte may further include an additive, optionally. For example, the additive may include an anode film-forming additive, a cathode film-forming additive, or an additive that can improve certain battery characteristics, such as an additive that improves the overcharge characteristics of the battery, or an additive that improves the high-temperature or low-temperature characteristics of the battery.

[0146] In some embodiments, the secondary battery may include an exterior body that is useful for enclosing the electrode assembly and electrolyte.

[0147] In some embodiments, the exterior body of the secondary battery may be a hard case such as a hard plastic case, an aluminum case, or a steel case. The exterior body of the secondary battery may be a soft bag such as a pouch-type soft bag. The material of the soft bag may be plastic such as at least one of polypropylene, polybutylene terephthalate, and polybutylene succinate. The present application does not particularly limit the shape of the secondary battery, and the secondary battery may be cylindrical, rectangular, or any other shape. For example, FIGS. 4 and 5 show an example of a secondary battery 1 having a rectangular structure.

[0148] In some embodiments, the secondary battery 1 includes an exterior body 11. The exterior body 11 includes a top cover assembly 111 and a case 112. An electrode assembly 12 composed of a positive electrode sheet, a negative electrode sheet, and a separator is housed in the case 112, and an electrolyte is also housed in the case 112. The positive electrode sheet or the negative electrode sheet includes a tab. When the secondary battery 1 is charged and discharged, active ions are inserted and removed by reciprocating between the positive electrode sheet and the negative electrode sheet. The electrolyte plays a role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is disposed between the positive electrode sheet and the negative electrode sheet, and mainly plays a role of preventing short-circuiting of the positive and negative electrodes, while allowing the active ions to pass through. Specifically, the secondary battery 1 may be a wound or stacked type battery such as a lithium ion battery or a sodium ion battery, but is not limited thereto.

[0149] Optionally, the case 112 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate define a storage chamber. The case 112 has an opening communicating with the storage chamber, and the top cover assembly 111 can cover the opening to seal the storage chamber. The positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly 12 by a winding process or a lamination process. The electrode assembly 12 is sealed in the storage chamber. The electrolyte is impregnated into the electrode assembly 12. The number of electrode assemblies 12 included in the secondary battery 1 may be one or more types, and may be selected according to requirements by those skilled in the art.

[0150] In some embodiments, the secondary battery 1 can be assembled as a battery. The battery can be a battery module or a battery pack. For example, the number of secondary batteries 1 included in a battery module can be one or more types, and the specific number can be selected by one skilled in the art according to the application and capacity of the battery module.

[0151] FIG. 6 shows an example of a battery module 10. Referring to FIG. 6, in the battery module 10, the multiple secondary batteries 1 may be sequentially arranged along the longitudinal direction of the battery module 10. Of course, they may be arranged in any other manner. Furthermore, the multiple secondary batteries 1 may be fixed by a fastener. Optionally, the battery module 10 may further include a housing having an accommodation space for accommodating the multiple secondary batteries 1.

[0152] In some embodiments, the above battery module 10 may be further assembled into a battery pack. The number of battery modules 10 included in the battery pack may be one or more types, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery pack. Of course, the battery pack may be directly composed of multiple secondary batteries 1.

[0153] 7 and 8 show a battery pack 20 as an example. With reference to Fig. 7 and Fig. 8, the battery pack 20 may include a battery housing and a plurality of battery modules 10 arranged in the battery housing. The battery housing includes an upper housing 21 and a lower housing 22. The upper housing 21 can be covered by the lower housing 22 to form a closed space that houses the battery modules 10. The plurality of battery modules 10 may be arranged in any manner in the battery housing.

[0154] The present application further provides a power consuming device including at least one of the secondary battery, battery module, or battery pack according to the present application. The secondary battery, battery module, or battery pack can be used as a power source for the power consuming device, or as an energy storage unit for the power consuming device. The power consuming device may be, but is not limited to, a mobile device (e.g., mobile phone, laptop, etc.), an electric vehicle (e.g., pure electric vehicle, hybrid electric vehicle, plug-in hybrid electric vehicle, electric bicycle, electric scooter, electric golf cart, electric truck, etc.), a train, a ship, and an artificial satellite, an energy storage system, etc. The power consuming device may select the secondary battery, battery module, or battery pack according to its usage requirements.

[0155] FIG. 9 shows an example of a power consumption device 30. The power consumption device 30 may be a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, etc. A battery pack or a battery module may be employed to meet the high power and high energy density requirements of the secondary battery required by the power consumption device 30. Other examples of the device may be a mobile phone, a tablet computer, a notebook computer, etc. These devices generally require light weight and thinness, and therefore may employ a secondary battery as a power source. Working Example

[0156] The following examples of the present application are described. The examples described below are illustrative and are used only to explain the present application, and should not be understood as limiting the present application. If no specific techniques or conditions are specified in the examples, they are performed according to the techniques or conditions described in the technical literature or according to the product instructions. If no manufacturer is specified, the reagents or equipment used are all ordinary products available on the market. Example 1 1. Manufacturing of positive electrode sheets

[0157] The positive electrode current collector was an 8 μm thick aluminum foil. 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (NCM333), conductive carbon black, and polyvinylidene fluoride (PVDF) binder were mixed in a suitable amount of N-methylpyrrolidone (NMP) solvent in a weight ratio of 93:2:5 with sufficient stirring to form a uniform positive electrode slurry. This positive electrode slurry was applied to the surface of the positive electrode current collector, and after drying and other processes, a positive electrode sheet was obtained. 2. Manufacturing of negative electrode sheets 2.1 Production of negative electrode active material

[0158] The hard carbon including the porous carbon skeleton was placed in a heating chamber of a vapor deposition furnace, and the heating chamber was evacuated to a relative vacuum of 100 Pa to 800 Pa using a vacuum pump.

[0159] Nitrogen gas was introduced into the heating chamber, and after the heating chamber was filled with nitrogen gas, a gas containing a silicon precursor was introduced into the heating chamber, and the gas flow rate ratio of the gas containing a silicon precursor to the protective gas was 5:1.

[0160] The heating chamber was heated to 600°C and kept at that temperature for 5 h, while the vapor deposition furnace was maintained at a positive pressure. The gas containing the silicon precursor was decomposed into silicon nanoparticles, which were then deposited in the pores and / or on the surface of the hard carbon to obtain a silicon-carbon composite.

[0161] After the temperature was maintained in the heating chamber, the introduction of the gas containing the silicon precursor was stopped, and after the silicon nanoparticles were allowed to cool naturally, the introduction of the nitrogen gas was stopped. 2.2 Manufacturing of negative electrode sheet

[0162] The negative electrode active material (silicon-carbon composite), conductive carbon black, thickener sodium carboxymethylcellulose (CMC), and binder styrene butadiene rubber emulsion (SBR) were mixed in an appropriate amount of deionized water in a weight ratio of 96.5:1.0:1.0:1.5 with sufficient stirring to form a uniform negative electrode slurry. This negative electrode slurry was applied to the negative electrode current collector, and after drying and other processes, a negative electrode sheet was obtained. 3. Electrolyte production

[0163] Ethylene carbonate (EC), methyl ethyl carbonate (EMC), and diethyl carbonate (DEC) were mixed in a volume ratio of 1:1:1 to obtain an organic solvent. Then, thoroughly dried lithium salt LiPF6 was dissolved in the mixed organic solvent to produce an electrolyte solution with a concentration of 1 mol / L. 4. Manufacturing of secondary batteries

[0164] A positive electrode sheet, a separator (PP / PE / PP composite thin film), and a negative electrode sheet were laminated in that order and wound up to form a battery cell. This was then placed in a housing, and the above-mentioned electrolyte was injected into the battery cell. After that, the cell was sealed, left to stand, hot and cold pressed, and chemically converted, resulting in a secondary battery. Examples 2 to 11

[0165] Compared to Example 1, the mass percentage distribution of carbon element and silicon element in the silicon-carbon composite is different, and in order to satisfy the mass percentage distribution of carbon element and silicon element, each Example can employ a negative electrode active material having a different particle size distribution, such as a different particle size Dv50 or Spin of hard carbon. Example 12

[0166] Example 12 differs from Example 1 in that non-porous hard carbon was used as the carbon matrix particles. Example 13

[0167] Example 13 differs from Example 1 in that non-porous graphite was used as the carbon matrix particles. Example 14

[0168] Example 14 differs from Example 1 in that the surface of the silicon-carbon composite is not covered with a conductive layer. Examples 15 to 18

[0169] Examples 15 to 18 differ from Example 1 in that hard carbons with different pore sizes and porosities were used. Example 19 and Example 20

[0170] Examples 19 and 20 differ from Example 1 in that silicon nanoparticles having different particle sizes were used. Examples 21 to 24

[0171] Examples 21 to 24 differ from Example 1 in that different conductive layer thicknesses were used. Example 25 and Example 26

[0172] Examples 25 and 26 differ from Example 1 in that different materials for the conductive layer are used. Examples 27 to 31

[0173] Examples 27 to 31 differ from Example 1 in that at least one of the particle diameter Dv50 and the particle diameter distribution spin is different. Comparative Example 1 to Comparative Example 2

[0174] The silicon-carbon composite differs from Example 1 in that the mass percentage distribution of carbon element and silicon element is different. In order to satisfy the mass percentage distribution of carbon element and silicon element, each Example can employ a negative electrode active material having a different particle size distribution, such as a different particle size Dv50 or Spin of hard carbon. Comparative Example 3

[0175] This embodiment differs from Example 1 in that a porous hard carbon on which silicon nanoparticles are not deposited and which is not covered with a conductive layer is used as the negative electrode active material.

[0176] Tables 1 to 7 show the parameters of the negative electrode active materials of the examples and comparative examples.

[0177] [Table 1]

[0178] [Table 2]

[0179] [Table 3]

[0180] [Table 4]

[0181] [Table 5]

[0182] [Table 6]

[0183] [Table 7]

[0184] In Tables 1 to 7, the process of controlling the porous structure of the carbon matrix particles is described by taking the case where the carbon matrix particles are hard carbon as an example. Biomass is pulverized as a carbon source, and one or more of coconut shells, bark, and fruit kernels are used as the biomass. The pulverized biomass is washed with an inorganic acid, and one or more of sulfuric acid, hydrochloric acid, and hydrofluoric acid can be used as the inorganic acid. The concentration of the inorganic acid is 1 mol / L to 5 mol / L, and the pickling time is 0.5 h to 2 h. After the pickling, the biomass is washed with deionized water to remove the residual acid, and then the biomass is pre-carbonized in an inert atmosphere. The inert gas may be one or more selected from nitrogen gas, argon gas, and helium gas. The pre-carbonization temperature is 400°C to 500°C, and the pre-carbonization time is 2 h to 5 h. The pre-carbonized biomass is carbonized at high temperature to obtain a porous carbon material. The carbonization temperature is 800°C to 1600°C, and the carbonization time is 2 h to 4 h. Characteristics Test Test part of negative electrode active material 1. Characterization of silicon and carbon element distribution in carbon-silicon composites

[0185] Elemental analysis of the ion-polished cross-section by energy spectrum method was performed in accordance with the GB-T17359-2012 test standard to test the element distribution of the particle cross-section. 2. Testing the silicon content in carbon-silicon composites

[0186] The silicon content was measured using an optical emission spectroscopy test (ICP: Inductively coupled plasma). Specifically, a carbon-silicon composite was used as a sample and the sample was digested using aqua regia and hydrofluoric acid (HF). An ICP test was then performed using a solution digested for 15 minutes and a solution that was completely digested. The silicon content in the solution digested for 45 minutes is the silicon content in the "periphery of the carbon-silicon composite", and the difference between the silicon content in the completely digested solution and the solution digested for 1 hour is the silicon content in the "central region of the carbon-silicon composite". 3. Testing the carbon content in carbon-silicon composites

[0187] The carbon-sulfur content analysis using infrared absorption method was performed in accordance with the GB / T20123-2006 test standard. Specifically, a carbon-silicon composite was used as the sample, and the carbon content after 20 minutes of testing was defined as the carbon content in the "periphery of the carbon-silicon composite." The difference between the carbon contents at 20 minutes and the end of the test was defined as the carbon content in the "periphery of the carbon-silicon composite." 4. Testing the minor axis r of carbon-silicon composite

[0188] The minor axis r was measured by a three-axis characteristic evaluation method, specifically, the minor axis r was measured on a planar projection of the carbon-silicon composite. 5. Measurement of Dv10, Dv90, and Dv50 of negative electrode active material

[0189] Using a laser diffraction particle size distribution analyzer (Malvern Mastersizer 3000), the particle size distribution was measured in accordance with the particle size distribution laser diffraction method GB / T19077-2016, and Dv10, Dv90, and Dv50 were obtained, from which (Dv90-Dv10) / Dv50 was calculated. 6. BET measurement of the specific surface area of ​​the negative electrode active material

[0190] The specific surface area measurement by gas adsorption method was performed in accordance with the GB / T19587-2017 test standard. Specifically, the negative active material was used as a sample, the sample tube was immersed in liquid nitrogen at -196°C, and the amount of nitrogen adsorbed on the solid surface at each pressure was measured at a relative pressure of 0.05 to 0.30. The amount of monolayer adsorption of the sample was calculated based on the BET multilayer adsorption theory and its formula, and the specific surface area of ​​the negative active material was calculated.

[0191] BET formula:

number

[0192] It was measured by gas displacement method according to GB / T 24586. Porosity P=(V1-V2) / V1*100%, where V1 is the apparent volume of the sample and V2 is the true volume of the sample. 8. Measurement of pore size of carbon matrix particles

[0193] The pore size test by gas adsorption method was conducted in accordance with GB / T19587-2017&GB / T21650.2-2008 test standards. Specifically, the silicon-carbon composite was used as the sample, the sample tube was immersed in liquid nitrogen at -196℃, and nitrogen gas was adsorbed into the material under a relative pressure of 0~1. The pore size distribution of the porous material was characterized based on the relationship diagram between the volume of each pore and the corresponding partial pressure. 9. Measurement of particle size D of silicon nanoparticles

[0194] The samples were tested according to the JIS / K0131-1996 test standard to obtain the XRD pattern, and the half-peak width β and the diffraction angle θ of the Si(111) crystal plane were calculated based on the XRD pattern of the samples by substituting them into the Debye-Scherrer equation to obtain the particle size of the nanosilicon particles. The Debye-Scherrer equation is Dhkl=k·λ / (βcosθ).

[0195] In the formula, Dhkl represents the particle size of the nanosilicon particles (unit: nm), k represents the Scherrer constant, which is 0.89, λ represents the wavelength of the incident X-ray, which is 0.15406 nm, β represents the half-peak width of the diffraction peak (unit: rad), and θ represents the diffraction angle (unit: degree). 10. Conductive layer thickness measurement

[0196] Scanning electron microscopy was used to measure the topography of the ion-polished cross-section of the sample in accordance with the JY / T010-1996 test standard, and the thickness of the conductive coating layer outside the material body was measured based on the cross-sectional topography. Testing the cycle characteristics of secondary batteries 1. Testing the room temperature cycle characteristics of secondary batteries

[0197] The test conditions were room temperature, and the fabricated secondary battery was charged at a rate of 0.5C and discharged at a rate of 0.5C, and a cycle test of full charge and full discharge was performed. When the capacity of the secondary battery had decayed to 80% of its initial capacity, the test was stopped and the number of cycles was recorded.

[0198] The secondary battery was allowed to stand at room temperature for 30 minutes, then charged to 4.2 V at a constant current of 0.5 C, further charged to 0.05 C at a constant voltage of 4.2 V, allowed to stand for 5 minutes, and then discharged to 2.8 V at a constant current of 0.5 C. This was considered as one charge / discharge cycle, and the discharge capacity this time was considered the initial discharge capacity of the battery. The battery was subjected to a charge / discharge test of 1000 cycles using the method described above, and the discharge capacity after the 1000th cycle was recorded.

[0199] Capacity retention rate (%) of secondary battery after 1000 cycles = (discharge capacity after 1000 cycles / discharge capacity after first cycle) x 100% 2. Testing the cycle characteristics of secondary batteries at 45℃

[0200] The test conditions were set at 45°C, and the fabricated secondary battery was charged at a rate of 1C and discharged at a rate of 1C, and a cycle test of full charge and full discharge was performed. When the capacity of the secondary battery had decayed to 80% of its initial capacity, the test was stopped and the number of cycles was recorded.

[0201] The secondary battery was allowed to stand at 45°C for 30 minutes, then charged to 4.2 V at a constant current of 1 C, further charged to 0.05 C at a constant voltage of 4.2 V, allowed to stand for 5 minutes, and then discharged to 2.8 V at a constant current of 1 C. This was considered as one charge-discharge cycle, and the discharge capacity this time was considered the initial discharge capacity of the battery. The battery was subjected to a charge-discharge test of 1000 cycles using the method described above, and the discharge capacity after the 1000th cycle was recorded.

[0202] Capacity retention rate (%) of secondary battery after 1000 cycles = (discharge capacity after 1000 cycles / discharge capacity after first cycle) x 100% Test results

[0203] The effect of the negative electrode active material of the present invention in improving the cycle characteristics of a secondary battery is shown in Tables 8 to 11.

[0204] [Table 8]

[0205] As can be seen from Table 8, in comparison with Comparative Example 1 and Comparative Example 2, in Examples 1 to 11, when silicon nanoparticles are uniformly deposited on the carbon skeleton, the cycle characteristics of the secondary battery are excellent. By setting 0.8≦B1 / A1≦2.5, particularly 1≦B1 / A1≦1.5, silicon nanoparticles can be uniformly deposited in the pores of the carbon skeleton, effectively suppressing the expansion of silicon nanoparticles during the cycle of the secondary battery, improving the structural stability of the negative electrode active material, and further improving the cycle characteristics of the secondary battery. Furthermore, by setting 1.05≦A2 / B2≦50, particularly 1.05≦A2 / B2≦3, silicon nanoparticles can be more uniformly deposited on the entire structure of the carbon skeleton, and the cycle characteristics of the secondary battery can be further improved. Furthermore, by setting 1≦A / B≦3, particularly 1.3≦A / B≦2, silicon nanoparticles can be more uniformly deposited on the entire structure of the carbon skeleton, and the cycle characteristics of the secondary battery can be further improved.

[0206] [Table 9]

[0207] As can be seen from Table 9, in Comparative Example 3, silicon nanoparticles are not deposited on the hard carbon, and the overall cycle characteristics are poor. Compared with Comparative Example 3, in Examples 12 to 13, deposition of silicon nanoparticles on non-porous hard carbon can improve the structural stability of the negative electrode active material to a certain extent. In Example 1, deposition of silicon nanoparticles in the porous hard carbon can greatly improve the structural stability of the negative electrode active material and improve the cycle characteristics of the secondary battery. Compared with Example 14, in Example 1, the conductivity of the secondary battery can be further improved by forming a conductive layer on the surface of the silicon-carbon composite.

[0208] [Table 10]

[0209] As can be seen from Table 10, in Examples 1, 15 and 18, the deposition effect of silicon nanoparticles can be adjusted by controlling the pore size and porosity of the hard carbon, and the structural stability of the negative electrode active material can be controlled.

[0210] In Examples 19 and 20, the particle size of the silicon nanoparticles is controlled, thereby making it possible to appropriately control the properties of the silicon-carbon composite.

[0211] In Examples 21 to 26, the conductive layer of the negative electrode active material is controlled, thereby improving the conductive properties of the negative electrode active material.

[0212] [Table 11]

[0213] As can be seen from Table 11, in Examples 27 to 31, by controlling the particle size of the negative electrode active material, the characteristics of the negative electrode active material can be improved, and the cycle characteristics of the secondary battery can be improved.

[0214] Although the present application has been described with reference to the preferred embodiments, various modifications may be made and the elements thereof may be replaced with equivalents without departing from the scope of the present application. In particular, the technical features described in each embodiment may be combined in any manner, as long as there is no structural conflict. The present application is not limited to the specific embodiments disclosed in this specification, but includes all technical solutions falling within the scope of the claims.

Claims

1. Carbon matrix particles having a carbon skeleton; and silicon nanoparticles attached to the carbon skeleton of the carbon matrix particles. In the outer peripheral region of the carbon-silicon composite, the mass percentage A of the carbon element of the carbon-silicon composite with respect to the total mass of the carbon-silicon composite 1 and the mass percentage B of the silicon element of the carbon-silicon composite relative to the total mass of the carbon-silicon composite. 1 That is, 0.8≦B 1 / A 1 ≦2.5 is satisfied, The outer peripheral region of the carbon-silicon composite is a region extending from the outer surface of the carbon-silicon composite toward the inside of the carbon-silicon composite within a distance of r / 2, where r represents the minor axis of the carbon-silicon composite; In a central region of the carbon-silicon composite, a mass percentage A 2 of the carbon element of the carbon-silicon composite relative to the total mass of the carbon-silicon composite and a mass percentage B 2 of the silicon element of the carbon-silicon composite relative to the total mass of the carbon-silicon composite satisfy 1.05≦A 2 / B 2 ≦50; The central region of the carbon-silicon composite is a region that is located within a distance of r / 2 from the geometric center of the carbon-silicon composite.

2. In the central region of the carbon-silicon composite, the mass percentage A of the carbon element of the carbon-silicon composite relative to the total mass of the carbon-silicon composite 2 and the mass percentage B of the silicon element of the carbon-silicon composite relative to the total mass of the carbon-silicon composite. 2 That is, 1.05≦A 2 / B 2 ≦3 is satisfied, 2. The negative electrode active material according to claim 1, wherein the central region of the carbon-silicon composite is a region that is within a distance of r / 2 from the geometric center of the carbon-silicon composite.

3. 3. The negative electrode active material according to claim 1, wherein mass percentage A of the carbon element in the carbon-silicon composite relative to the total mass of the carbon-silicon composite tends to decrease in a direction from a geometric center of the carbon-silicon composite toward an outer surface of the carbon-silicon composite, and mass percentage B of the silicon element in the carbon-silicon composite relative to the total mass of the carbon-silicon composite tends to increase in a direction from the geometric center of the carbon-silicon composite toward an outer surface of the carbon-silicon composite.

4. The negative electrode active material described in claim 3, wherein a mass percentage A of the carbon element of the carbon-silicon composite relative to the total mass of the carbon-silicon composite and a mass percentage B of the silicon element of the carbon-silicon composite relative to the total mass of the carbon-silicon composite further satisfy 1≦A / B≦3.

5. The negative electrode active material according to claim 1 or 2, wherein the carbon matrix particles include one or more of graphite, soft carbon, and hard carbon.

6. the carbon skeleton is a porous carbon skeleton and the silicon nanoparticles are within the pores and / or on the surface of the porous carbon skeleton; the porous carbon skeleton comprises pores extending through the carbon skeleton; The pores have a diameter of 1 nm to 200 nm; 3. The negative electrode active material according to claim 1, wherein the porosity of the porous carbon skeleton is 40% to 70%.

7. The negative electrode active material according to claim 1 or 2, wherein the particle diameter D of the silicon nanoparticles is D≦10 nm.

8. 3. The negative electrode active material according to claim 1, further comprising a conductive layer covering the carbon-silicon composite.

9. 9. The negative electrode active material of claim 8, wherein the conductive layer has a thickness of ≦3.5 μm.

10. the conductive layer comprises a carbon layer and / or a conductive polymer layer; 9. The negative electrode active material of claim 8, wherein the conductive polymer layer comprises one or more of polyaniline, polypyrrole, polyacetylene, polythiophene, polyphenylene sulfide, and polyparaphenylene.

11. The average particle size Dv50 of the negative electrode active material is 5 μm≦Dv50≦11 μm, 3. The negative electrode active material according to claim 1, wherein average particle diameters Dv90, Dv10 and Dv50 of the negative electrode active material satisfy (Dv90-Dv10) / Dv50≦1.

4.

12. The specific surface area BET of the negative electrode active material is BET≦4 m 2 The negative electrode active material according to claim 1 or 2, wherein the molecular weight is 1 / g.

13. A method for producing a negative electrode active material, comprising the steps of: A step S100 of supplying a gas containing a silicon precursor to carbon matrix particles having a carbon skeleton; and S200 producing silicon nanoparticles attached to the carbon skeleton from the silicon precursor by chemical vapor deposition to obtain a carbon-silicon composite; In the outer peripheral region of the carbon-silicon composite, the mass percentage A of the carbon element of the carbon-silicon composite with respect to the total mass of the carbon-silicon composite 1 and the mass percentage B of the silicon element of the carbon-silicon composite relative to the total mass of the carbon-silicon composite. 1 That is, 0.8≦B 1 / A 1 ≦2.5 is satisfied, The outer peripheral region of the carbon-silicon composite is a region extending from the outer surface of the carbon-silicon composite toward the inside of the carbon-silicon composite within a distance of r / 2, In a central region of the carbon-silicon composite, a mass percentage A 2 of the carbon element of the carbon-silicon composite relative to the total mass of the carbon-silicon composite and a mass percentage B 2 of the silicon element of the carbon-silicon composite relative to the total mass of the carbon-silicon composite satisfy 1.05≦A 2 / B 2 ≦50; The method for producing a negative electrode active material, wherein the central region of the carbon-silicon composite is a region that is at a distance of r / 2 or less from the geometric center of the carbon-silicon composite.

14. The method of claim 13, further comprising the step S300 of forming a conductive layer on the silicon-carbon composite.

15. A secondary battery comprising the negative electrode active material according to claim 1.

16. A battery module comprising the secondary battery according to claim 15.

17. A battery pack comprising the battery module according to claim 16.

18. A power consuming device comprising the secondary battery according to claim 15, the battery module according to claim 16, or the battery pack according to claim 17.

Citation Information

Patent Citations

  • NANO silicon composite negative electrode material for lithium ion battery, production method and lithium ion battery

    JP2016134382A

  • Novel material having highly durable lithium insertion and method for manufacturing the same

    JP2018534720A

  • Electroactive Materials for Metal-Ion Batteries

    JP2022506882A

  • Electroactive materials for metal-ion batteries

    JP2023536191A

  • Silicon carbon composite and its manufacturing method

    JP2023547418A